'Don't take a poo!': Worker misbehaviour in on‐demand ride‐hail carpooling. (18th February 2020) - Reid‐Musson, Emily; MacEachen, Ellen; Bartel, Emma
Abstract : Workers actively negotiate contradictions between discourses of flexibility and entrepreneurialism and actually existing conditions of risk and precarity endemic to online self‐employed work. This article examines how ride‐hail drivers counter‐branded UberPool—a carpool ride‐hail service—as 'UberPoo'. While marketed as a solution to congestion, UberPool created risky and coercive working conditions for ride‐hail drivers. Our analysis is from a study on ride‐hail driver experiences of health and safety risks in a large Canadian city. We engage the concept of organisational misbehaviour to explore how drivers mocked and avoided carpool rides despite the threat of penalties. We characterise misbehaviour as a struggle over lack of control and lack of autonomy in self‐employed work, providing evidence that despite their structural powerlessness, some ride‐hail drivers do set limits around the work they are willing to accept. Algorithmic management and ambiguously classified ride‐hail work are thus subject to some degree of subversion.